2021
DOI: 10.1186/s12887-021-02529-y
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-related difficulties in healthy children and adolescents

Abstract: Background As sleep-related difficulties are a growing public health concern, it is important to gain an overview of the specific difficulty areas of the most vulnerable individuals: children. The current descriptive study presents the prevalence of sleep-related difficulties in two large samples of healthy children and adolescents and outlines the effects of age, gender, and socioeconomic status (SES) on various sleep-related difficulties. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 48 publications
5
42
3
Order By: Relevance
“…Analyzing the CSHQ subscales, in children attending primary school we observed more bedtime resistance, sleep anxiety, and night wakings according to previous reports in the literature. 16 , 20 22 Consistent with previous findings, 23 , 24 higher sleep duration score was reported in secondary school students. The sleep duration decreases physiologically as children grow older.…”
Section: Discussionsupporting
confidence: 89%
“…Analyzing the CSHQ subscales, in children attending primary school we observed more bedtime resistance, sleep anxiety, and night wakings according to previous reports in the literature. 16 , 20 22 Consistent with previous findings, 23 , 24 higher sleep duration score was reported in secondary school students. The sleep duration decreases physiologically as children grow older.…”
Section: Discussionsupporting
confidence: 89%
“…The effect of age was allowed to vary across participants and controlled for differences in the number of days between BMI assessments across participants. Variables were selected a priori for inclusion in the model based on theory [ 26 , 27 ] and previous research demonstrating differences in children’s sleep across sex [ 55 ], race [ 56 ], age [ 57 ], and chronotype [ 58 ]. Using a theoretically driven step-down modeling approach, variables were tested to determine if they should be included as a covariate or allowed to interact with the school-year (Age-P1) and summer slopes (Age-P2).…”
Section: Methodsmentioning
confidence: 99%
“…The effect of age was allowed to vary across participants and controlled for differences in the number of days between BMI assessments across participants. Variables were selected a priori for inclusion in the model based on theory [26,27] and previous research demonstrating differences in children's sleep across sex [55], race [56], age [57], and chronotype [58].…”
Section: Statistical Design and Analysismentioning
confidence: 99%
“…In addition, Conklin suggested that chronic sleep deprivation measured by selfreported questionnaire among adolescents aged 13-18 years old increased the risk of major depression among young women [13]; and Rajab demonstrated an association between sleep measured by self-reported questionnaire and mental health including depressive symptoms and severe stress, in which severe stress was negatively associated with sleep in girls but not in boys among adolescents in grade 7-12 [14]. Finally, Lewien suggested that sleep-related difficulties are more frequent among girls than in boys in adolescents aged 10-17 years old, measured by self-reported questionnaires [15].…”
Section: Introductionmentioning
confidence: 97%